Genetic Differentiation in the Oh-Shamo (Japanese Large Game) Breed of Chickens Assessed by Microsatellite DNA Polymorphisms - Oka, Takao; Tsudzuki , Masaoki (International Journal of Poultry Science, 2014)
The Oh-Shamo is a native Japanese chicken breed that has been improved for cock fighting purpose for approximately 400 years. Two types of Oh-Shamo have been created: one type concentrates on offence and the other type is specialized for defense. In addition to these Oh-Shamo types for cock fighting, commercial stocks have been established to produce brand meat in Japan. In this article, we revealed the genetic differentiation among Oh-Shamo populations based on the difference in the use and the manner of fighting, as well as genetic diversity in these populations. MNA, AR, HO and HE were 2.55-4.03, 2.52-3.75, 0.420-0.577 and 0.422-0.559, respectively, throughout both fighting- and meat-purpose populations. There was a tendency for fighting-type Oh-Shamo populations to show higher genetic diversity. Inbreeding was not observed in both fighting-purpose and meat-purpose Oh-Shamo populations. Neighbor-joining tree topology based on DPS genetic distance clearly separated fighting-purpose Oh-Shamo from meat-purpose Oh-Shamo. Thus, commercial Oh-Shamo for meat production is genetically distinct from the original Oh-Shamo used for cock fighting. On the other hand, no conspicuous genetic differentiation was observed between offence- and defense-types of fighting-purpose Oh-Shamo.